Penerapan Model Pembelajaran Deep Dialog untuk Pengembangan Kemampuan Berpikir Kritis dalam Pembelajaran Sejarah Siswa Kelas XI IPS SMA Negeri 5 Banda Aceh - Desi Rianti; Mawardi '; Sufandi Iswanto (Universitas Syiah Kuala, 2020)
The learning model plays an important role in the learning process, the problem in this research is that during the question and answer process, students still have not found a way of thinking critically. The purpose of this research was to study how the contribution model of deep dialogue learning to critical thinking skills in the history learning of students class XI IPS Senior High School N 5 Banda Aceh. Qualitative research methods with descriptive research type. Data convincing techniques in this study are tests of critical thinking skills and interviews. Based on the results of the recognized research was the average value of the ability aspect gives a simple explanation 42.25%, recognize and solve problems 36.00%, and ability to conclude is 46.00%. Then from these data obtained an average percentage of the ability of critical test results in the Japanese occupation of Indonesia as a whole which is 45%. Thus, the average critical thinking ability student of grade XI IPS Senior High School N 5 Banda Aceh is classified in the low category. The inactivity model of deep dialogue learning towards the critical thinking ability is caused less optimal classroom management in the learning process, so that the time needed to get all the steps is insufficient. Students could not do analytical problems. Then this becomes a challenge for them in the learning process carried out following the critical thinking process.